2021
DOI: 10.1016/j.vaccine.2021.03.027
|View full text |Cite
|
Sign up to set email alerts
|

U.S. public support for COVID-19 vaccine donation to low- and middle-income countries during the COVID-19 pandemic

Abstract: As COVID-19 vaccines become available to the public, there will be a massive worldwide distribution effort. Vaccine distribution has historically been unequal primarily due to the inability of nations with developing economies to purchase enough vaccine to fully vaccinate their populations. Inequitable access to COVID-19 vaccines will not just cause humanitarian suffering, it will likely also be associated with increased economic suffering worldwide. This study focuses on the U.S. population and its beliefs ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…The elderly are the primary susceptible group. Statistical data from China, United States, and India also show a higher mortality rate among elderly COVID-19-infected persons (29,54,55). Consequently, the older the people are, the stronger they have the intention to be vaccinated.…”
Section: Estimation Of Participants Selecting the Covid-19 Vaccinementioning
confidence: 99%
“…The elderly are the primary susceptible group. Statistical data from China, United States, and India also show a higher mortality rate among elderly COVID-19-infected persons (29,54,55). Consequently, the older the people are, the stronger they have the intention to be vaccinated.…”
Section: Estimation Of Participants Selecting the Covid-19 Vaccinementioning
confidence: 99%
“…However, vaccine donations, regardless of whether they are a result of vaccine empathy or vaccine diplomacy, could have a positive impact on the ever-increasingly widening vaccine inequality. Interestingly, the results of our narrative review suggest that, different from the makeup of news reports or other insights in mass media [35][36][37], the majority of scholarly articles on vaccine diplomacy published amid the pandemic supported the practice [18,19,[25][26][27][28][29][31][32][33] with only two [22,30] of the twelve records expressing concerns about potential domestic backlash for donating vaccines. Our findings suggest that what WHO officials indicated on 11 May 2021, when they state that "vaccine diplomacy is not cooperation" and only "clear and clean cooperation" could yield benefits to pandemic prevention and control [42], might be in direct contrast to most academics' positions on vaccine diplomacy [18,19,[25][26][27][28][29][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the results of our narrative review suggest that, different from the makeup of news reports or other insights in mass media [35][36][37], the majority of scholarly articles on vaccine diplomacy published amid the pandemic supported the practice [18,19,[25][26][27][28][29][31][32][33] with only two [22,30] of the twelve records expressing concerns about potential domestic backlash for donating vaccines. Our findings suggest that what WHO officials indicated on 11 May 2021, when they state that "vaccine diplomacy is not cooperation" and only "clear and clean cooperation" could yield benefits to pandemic prevention and control [42], might be in direct contrast to most academics' positions on vaccine diplomacy [18,19,[25][26][27][28][29][31][32][33]. While some criticisms towards vaccine diplomacy seem to be not completely unfounded, as the scale and severity of COVID-19 might make any potential future expected gains associated with these donations seem uncaring, possibly bordering on unsympathetic [19], the significance of the potential sustainability of vaccine diplomacy, which has deeper and stronger roots in multilateral cooperation and collaboration compared with vaccine empathy, along with how this sustainability might impact COVID-19 vaccine donations in the long run, should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inequality in the distribution of vaccines has always existed in the past as evident from the H1N1 Influenza outbreak in 2009 when vaccine supplies were completely dominated by developed rich countries. 2,3 Recent studies have shown that, with limited healthcare-related services, LMICs are more likely to have a higher infection and mortality rate as compared to HICs. Richard Hatchett, head of Coalition for Epidemic Preparedness Innovations (CEPI) said that "If COVID-19 vaccines are misallocated in the way they were in 2009, the pandemic will last longer, more people will die and the disruption will be greater than it needs to be".…”
Section: To the Editormentioning
confidence: 99%